Paper and Electronic questionnaire - Kaddour, Nabila (Journal of Human Sciences, 2023)
This research deals with the methodological steps by which the paper and electronic questionnaire are designed, the stages that must be followed, its components, and how to prepare its content. Therefore, it is mainly directed to a wide range of students and researchers in the field of field studies, especially applied linguistics; As most of them believe that the questionnaire is just a set of questions that require a response only by the sample, so it is a very important stage unless its owner scrutinizes to clarify the real goals that he expects from behind collecting the data after distributing it to the participants. Therefore, this article attempts to answer the following problem: What is a paper questionnaire? What is the difference between it and electronic? How do you accomplish both of them?